Hyalinizing Clear Cell Carcinoma of Buccal Vestibule: A Rare Case - Saede Atarbashi Moghadam; Fazele Atarbashi Moghadam; Maryam Shahla; Sara Bagheri (Mashhad University of Medical Sciences, 2013)
Hyalinizying clear cell carcinoma is a rare tumor which affects women more than men and is more common in minor salivary glands. The purpose of this paper was to describe a case of hyalinizing clear cell carcinoma of buccal vestibule in a 55-year-old woman. It is important to differentiate this neoplasm from other tumors with clear cell features because of their differences in treatment and clinical outcome